Pelatihan Parenting Untuk Meningkatkan Keterampilan Mengasuh Anak di Era Digital: Studi pada kegiatan Pelatihan Orang Tua Anak Kober Arafah Kota Bandung - Asep Saepudin; Hasan Tafsir Maulana; Gumilar Fauzi Darsono; Hanifah Rachmadanti; Ani Rindiani (LPPM Universitas Koperasi Indonesia, 2023)
Parenting is increasingly complex, especially in the digital era, with many problems related to the impact of technology on children's development. Therefore, parenting training in the digital era is important to implement, this paper is to explore the importance of parenting training in the digital era and how this training can improve the skills of parents at Kober Arafah in caring for children in the digital era. The purpose of this paper is to evaluate the process of organizing Child Care Parenting Training in the Digital Era. The training participants are parents who have early childhood in Kober Arafah. The results of the training show significant changes in parents' understanding and skills in dealing with the challenges of parenting in the digital era. The post-test scores showed a significant increase compared to the pre-test scores, indicating the effectiveness of the training. In conclusion, parenting training in the digital era has an important role in enhancing parents' skills in caring for children in the digital era, helping them face challenges and maintain the safety and well-being of their children in an increasingly complex digital world